PELATIHAN TRIK PENGUASAAN KEMAMPUAN BERBICARA DALAM BAHASA INGGRIS BAGI SISWA LKP ROYAL SKILL TRAINING CENTER - Akmal; Zulkarnain Sirait; Suparmadi; Gunawan Syahputra (DEVELOPMENT: Journal of Community Engagement, 2025)
This training is to give the method how to master to speak the English for the students of LKP Royal Skill Training Center. They do not have basic skill of speaking the English. The speakers tell about the technique to study speak English step by step. The methods are used in the descriptions in the field or the location. The students are studying to focus on the computer at the LKP Royal Skill Training Center, they are 18 (eighteen) students or the participants. They are 3 (three) methods to master the speaking English, namely: speak to themselves, to watch the western movie and listen to the English music or songs, the last is to give the respon from the speakers who talk about the materials in English so the listeners or the students have to respon in English so that they will have good habits in English by speaking in English. A few students give the respon by asking the questions and the speakers. The participants are so happy in the training because they have had tricks to master speaking English step by step by doing themselves.